2008
DOI: 10.1083/jcb.200810060
|View full text |Cite
|
Sign up to set email alerts
|

Traction stress in focal adhesions correlates biphasically with actin retrograde flow speed

Abstract: Abbreviations used in this paper: CA-Rac, constitutively active Rac1; FA, focal adhesion; FSM, fl uorescent speckle microscopy; PAA, polyacrylamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

64
469
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 440 publications
(536 citation statements)
references
References 27 publications
64
469
2
1
Order By: Relevance
“…3H). EA-TIRFM of αV-GFPconstrained in blebbistatin-treated cells revealed higher levels of anisotropy in NA where retrograde flow remained intact, but very low levels in the cell interior where retrograde flow was blocked (25) (Fig. 3I).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3H). EA-TIRFM of αV-GFPconstrained in blebbistatin-treated cells revealed higher levels of anisotropy in NA where retrograde flow remained intact, but very low levels in the cell interior where retrograde flow was blocked (25) (Fig. 3I).…”
Section: Resultsmentioning
confidence: 99%
“…As there is no reliable way to block all retrograde flow or alter its rate without disrupting F-actin integrity, we instead asked whether there was a regional correlation between F-actin flow and integrin alignment. We used the myosin-II inhibitor blebbistatin, which abolishes myosin-II-driven flow in the lamella and FAs, but leaves actin polymerization-driven flow and cytoskeletal integrity in the lamellipodium intact (25). As expected, blebbistatin eliminated cell polarity and blocked FA elongation, leaving a rim of diffraction-limited nascent adhesions (NAs) in lamellipodia (26) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…12,30,31 Furthermore, an effective connection of actin filaments to FAs can cause a deceleration of actin flow. 32,33 Keratinocytes were transfected with GFP-actin. Defined, small regions of GFP-labeled filopodial actin bundles were bleached to visualize retrograde flow ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have revealed a close connection between actomyosin dynamics and traction stresses exerted by the cell (45,46). Given our observations of traction stress modulation, we proceeded to examine how the spatial distribution and dynamics of the actomyosin cytoskeleton are regulated by MT dynamics and Rho kinase activity.…”
Section: Mt Network Forms a Radially Emanating Dynamic Array During Tmentioning
confidence: 99%